Anxiety Problems Encountered by the Students in Learning English Speaking Skill - Khairunnisa Khairunnisa; Sofyan A. Gani; Diana Achmad (Research in English and Education Journal, 2022)
This is a library research. This study aims to investigate the factors that can cause the students to feel anxious in speaking English according to some literatures. Meanwhile, the object of this study is experts’ opinions about factors that made students feel anxious in speaking English. The data of this study are the anxiety felt by students in speaking English. There were 5 literatures as references to collect the data. In collecting data, the researcher used content analysis. First, the researcher found some references such as books, journals, and articles. Then, the researcher read and selected the needed data based on the research objective. After reviewing five references of previous studies regarding factors that cause students’ anxiety in speaking English, the researcher concluded that the are some factors generating anxiety of EFL students; low self-esteem, presentation in the classroom, fear of making mistakes, communication apprehension, test anxiety, negative evaluation, teaching testing procedure, fear of taking risks, teacher manner, and learner’s belief. The researcher suggests students who suffer anxiety here should be able to analyse their own problem in speaking performance in order to find thesolution to decrease it. Another suggestion is teachers should be able to understand students’ characteristics to analyse their problem related to anxiety before finding the way to reduce it.